Analisis Pengaruh Bangunan Krib terhadap Kecepatan Aliran pada Tikungan Luar Sungai Kalibuntu menggunakan Pemodelan Numerik - Salsabila Rifdah Taufik; Bagas Nathaniel; Elkayoan Radita; Ririn Rimawan (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2025)
River morphology is a condition that is constantly changing due to erosion and sedimentation in certain parts of the river. However, erosion and sedimentation that occur in undesirable parts of the river can cause significant losses to humans. One of the villages that has the potential to experience damage due to river erosion is Kalibuntu Village where there has been a shift in the river channel that has approached the residential area and increased the risk of landslides. Based on this, the construction of river groynes is planned to prevent further erosion. The use of river groynes must be in accordance with the characteristics of the river and its surroundings. Selecting appropriate designs and materials is very important to achieve effective results in preventing river erosion. To obtain the effect of groynes on changes in the magnitude and direction of flow velocity at the Kalibuntu bend, numerical modeling was carried out using MIKE 21 - Curvilinear software which is a hydrodynamic model. This method was chosen because the software can describe the morphological response of the river with relatively good accuracy. The numerical model was carried out with 2 series of models, the first simulating the existing conditions of the river, while the second simulated the normalization of the river with installed groynes as per the planned design. When compared to previous studies, this study only focuses on the effect of groynes on flow velocity as depicted from the results of 2D modeling and validated using field observation data based on several approaches, while a further novelty is that similar research has not yet been conducted at the selected study location. Based on modeling of 4 river segments, the installation of groynes showed a reduction in average flow velocity by 0.04 m/s at the starting point segment just before the river bend, by 0.111 m/s at the outer bend of the river, by 0.124 m/s at the outer bend segment of the river downstream, and an increase in average flow velocity by 0.157 m/s at the inner bend segment of the river.